2019
DOI: 10.14235/bas.galenos.2018.2358
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches in Premenstrual Syndrome Management

Abstract: as premenstrual syndrome (PMS) (2). The late twenties and midfifties are the periods when PMS is seen commonly (3). In the premenstrual period, changes in appetite such as excessive eating and craving, weight gain, edema, breast tenderness, and swelling and pain in the joints, abdominal pain, stomach problems, back pain, headaches, vertigo and dizziness, sweating in hands and feet, fatigue, skin problems such as acne, insomnia and short-term drowsiness, decreased libido, depressive mood, anger outbursts, irrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…However, premenstrual symptoms occurring in the second half of the menstrual cycle negatively affect the lives of many women. 1 Premenstrual symptoms may cause many problems like mental health, physical and severe functional disorders occurring in women's social lives and work lives. Symptoms in adolescents may negatively affect academic performance and social interaction.…”
mentioning
confidence: 99%
“…However, premenstrual symptoms occurring in the second half of the menstrual cycle negatively affect the lives of many women. 1 Premenstrual symptoms may cause many problems like mental health, physical and severe functional disorders occurring in women's social lives and work lives. Symptoms in adolescents may negatively affect academic performance and social interaction.…”
mentioning
confidence: 99%
“…Consequently, allopregnanolone's lower concentration in the luteal phase causes aggression, depression, and mood anxiety. Certainly, women suffering from PMS showed low levels of allopregnanolone levels [ 6 ].…”
Section: Literature Review Based On Research Questionsmentioning
confidence: 99%
“…Eighty-five per cent of reproductive-age women experience at least one symptom of PMS, and 2.5–3% of women suffer from premenstrual dysphoric disorder (PMDD) [ 2 ]. It has been reported that women with PMS tend to have a significantly lower quality of life, legal problems, suicidal ideation, decreased work productivity, social isolation, parenting problems, increased absenteeism from work, impaired personal and social relationships, and more frequent visits to hospitals [ 2 , 5 , 6 ]. Additionally, PMS also leads to an increased tendency to have an accident, drug addiction, economic losses, and a decline in demic achievement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premenstrual somatic and psycho-behavioural symptoms are categorized by a cyclic pattern that is obvious within the luteal phase [1], and they significantly affect quality of life with more frequent visits to hospitals parenting problems, decreased work productivity, and impaired individual and societal relationships [2][3][4]. It is a common and recurrent gynaecological problem [1], and 20-30% of reproductive-age women experience clinically significant premenstrual syndrome (PMS) symptoms [5].…”
Section: Introductionmentioning
confidence: 99%